Ependymomas in infancy: underlying genetic alterations, histological features, and clinical outcome - Jünger, Stephanie T. (Childs Nerv Syst, 2020)
INTRODUCTION: Young age is an adverse prognostic factor in children with ependymomas. Treatment of these infants is challenging since beneficial therapeutic options are limited. As ependymomas are considered a biologically heterogeneous group, we aimed to characterize infant ependymomas with regard to their histological and genetic features. MATERIALS AND METHODS: We analyzed 28 ependymomas occurring in children younger than 18 months at diagnosis enrolled into the HIT2000-E protocols with the aim to postpone irradiation until the age of 18 months if possible. All cases underwent neuropathological review, including immunohistochemical characterization. Genome-wide copy number alterations (CNA) were assessed by molecular inversion probe assays, and RELA and YAP1 fusions were detected by RT-PCR and sequencing. RESULTS: All infant ependymomas were anaplastic (WHO grade III). Twenty-one (75%) cases were located in the posterior fossa. Gross total resection was accomplished in 12 (57%) of these cases. All posterior fossa tumors showed loss of H3-K27me(3) characteristic of PFA ependymomas. CNA analysis showed a stable genome in all cases with lack of chromosome 1q gain, an adverse prognostic marker in PFA ependymomas of older children. However, after a median follow-up of 5.4 years, 15 (71%) relapsed, and 9 (43%) died. Seven ependymomas (25%) occurred in the supratentorial region. Gross total resection could be achieved in only two of these cases. Four tumors carried C11orf95-RELA fusions, and two cases had typical YAP1-MAMLD1 fusions (one case was not analyzable). The RELA-fused cases did not display CDKN2A loss as an adverse indicator of prognosis in this disease entity. Although three infants (43%) with supratentorial ependymomas relapsed, all patients survived (median follow-up, 8.0 years). CONCLUSION: Infant ependymomas seem to fall into three biological entities, with supratentorial tumors carrying RELA or YAP fusions and PFA posterior fossa ependymomas. The latter showed a poor outcome even though chromosome 1q gain was absent.